Comparison of the Nutritional Properties and Transcriptome Profiling Between the Two Different Harvesting Periods of Auricularia polytricha - Wang, Wenliang; Wang, Yansheng; Gong, Zhiqing; Yang, Shifa; Jia, Fengjuan (Frontiers in Nutrition, 2021)
Auricularia polytricha (A. polytricha) is a functional food with numerous bio-active health-promoting compounds. The nutritional and medical properties of A. polytricha have been well studied, however, data about difference of nutritional properties and transcriptome profiling between different harvesting periods of A. polytricha were relatively reported. Here, nutritional properties and transcriptome analysis were compared between two different harvesting periods of A. polytricha: AP_S1 (the stage for the first harvesting period) and AP_S2 (the stage for the third harvesting period). Our results showed that AP_S1 had more growth advantages than AP_S2, including biomass, auricle area and thickness, protein and Ca contents, and most species of amino acid contents, which contributed to the higher sensory evaluation and acceptability of AP_S1. Transcriptome analysis showed that some synthesis and metabolic processes were strengthened in AP_S1, especially the synthesis and metabolism of amino acids and protein. Moreover, the enhanced energy metabolism pathways could provide more energy for AP_S1 to synthesize nutritional substance. To sum up, this study is the first to compare the nutritional properties and gene expression profiling between different harvesting periods of A. polytricha, and the results can present insights into the growth and genetic characteristics of A. polytricha.